1989
DOI: 10.2527/jas1989.67123445x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Magnesium Absorption and Metabolism in Ruminants

Abstract: Magnesium is a nutrient required for all animals, but it is especially critical for ruminants. A physiological deficiency of Mg results in hypomagnesemic tetany. Typically, only female ruminants are affected, and the disturbance usually occurs during the early stages of lactation. Magnesium functions at three biochemical levels, as a cofactor at the enzymatic level, at the structural level in assembly of ribosomes, and at the whole cell level as a stabilizing force in membranes. Parathyroid hormone (PTH) can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
5

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 56 publications
0
31
0
5
Order By: Relevance
“…Hence, differences in serum Mg can be attributed to this increased Mg intake, which was even twofold in the HD treatment. Blood Mg is not hormonally regulated to a constant level, but it is strongly affected by Ca regulation (Fontenot et al, 1989). In the current study, no differences were observed for Ca homeostasis indicators between treatments, so most likely the effects observed on Mg are due to differences in Mg supply.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, differences in serum Mg can be attributed to this increased Mg intake, which was even twofold in the HD treatment. Blood Mg is not hormonally regulated to a constant level, but it is strongly affected by Ca regulation (Fontenot et al, 1989). In the current study, no differences were observed for Ca homeostasis indicators between treatments, so most likely the effects observed on Mg are due to differences in Mg supply.…”
Section: Discussionmentioning
confidence: 99%
“…However, if influx is smaller than efflux, the relatively large Mg pools in the ICS or bones in a cow cannot acutely be mobilized to maintain physiological plasma Mg concentrations. Significant mobilization of Mg from bone appears to be unlikely because the ratio between Ca and Mg in bone is 42 to 1, and substantial withdrawal from bone would disrupt both Ca and pH homoeostasis (Fontenot, Allen, Bunce, & Goff, ). Furthermore, Mg absorption from the rumen is neither increased at hypomagnesemia (Martens & Stössel, ) nor stimulated by intravenous injection of PTH (parathyroid hormone) or PTHrP (parathyroid hormone‐related peptide; Dua, Leonhard, Martens, Abbas, & Care, ).…”
Section: Principles Of Mg Metabolismmentioning
confidence: 99%
“…The nitrate concentration of pasture herbage is also elevated after N fertilizer is applied, and is generally higher in grass than in mixed swards (Papadopoulos etal. 1993 (Mayland and Wilkinson 1989), increasing the risk of hypomagnesemia (Fontenot et al 1989). The hypomagnesemia and high intake of K may also affect Ca metabolism in a way that could precipitate parturient hypocalcemia (Fredeen 1992 (Beede 1992 (Kunelius and Sanderson 1990 (Wilson 1975).…”
mentioning
confidence: 99%